The Strategy Of Implementing Service Quality (Servqual) In Increasing The Competitiveness Of The Workshop Business Of Pt. Diamond Of Light In Bima City - Rizqi Illahi; Ihwan P. Syamsudin; Umar sagaf (JURNAL ECONOMINA, 2026)
The increasing number of workshop businesses in Bima City has triggered increasingly competitive competition, so that service quality is the main determinant in retaining customers. The problem in this study lies in the lack of optimal implementation of service quality at PT. Diamond Light, which has an impact on fluctuations in customer satisfaction and loyalty levels. This study aims to examine in depth the strategy of implementing Service Quality (SERVQUAL) in increasing the competitiveness of the workshop business. The research method used is qualitative with a descriptive approach, through data collection techniques in the form of field observations, interviews with management and customers, and documentation. Data analysis is carried out systematically through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the five dimensions of SERVQUAL tangibles, reliability, responsiveness, assurance, and empathy have been implemented, but have not been carried out consistently and comprehensively. The main weakness is seen in the aspect of responsiveness and attention to customer needs. Therefore, the necessary strategies include improving the professionalism of human resources, improving facilities and infrastructure, accelerating services, and strengthening more responsive and personalized communication. In conclusion, the targeted and sustainable implementation of SERVQUAL can strengthen customer satisfaction and directly increase the competitiveness of PT. Berdiamond Cahaya in the midst of dynamic workshop business competition